Kajian Linguistik Kognitif Terhadap Makna Leksikal dan Kiasan Kotowaza dalam Video YouTube - Firda Zahratul Fuadah (Universitas Diponegoro, 2026)
This study aims to analyze the lexical and figurative meanings of Japanese kotowaza in YouTube videos through a cognitive linguistic approach focusing on meaning construction and speakers’ cognitive perspectives in order to facilitate better understanding among Japanese learners. The data were examined through a descriptive-qualitative research approach, employing the observation and a note-taking technique. The study's data were gathered from YouTube videos, specifically from the channels Ask Japanese, TEDx, BUNCHAN Ch., and TOKYO VEG LIVE, which showcase naturally occurring Japanese language. The study's results reveal a connection between the lexical and figurative meanings of kotowaza, which aids Japanese language learners in grasping and memorizing these expressions. This understanding subsequently enhances their ability to utilize kotowaza effectively in Japanese communication.